Pertanggungjawaban Hukum atas Pencemaran Lingkungan Hidup Akibat Aktivitas Limbah Perusahaan melalui Mekanisme Gugatan Perwakilan Kelompok: Studi Kasus Putusan Nomor 29/Pdt.G/2023/PN.Skh (Pusat Riset dan Inovasi Nasional, 2026)
Industrial development in Indonesia has significantly contributed to national economic growth; however, it also poses potential risks of environmental pollution when corporate waste management is not conducted properly. Environmental pollution resulting from corporate waste activities may cause harm to surrounding communities, including health problems, ecosystem degradation, as well as material and immaterial losses. In this context, the class action mechanism serves as a relevant legal instrument to collectively advocate for the rights of affected communities. This study aims to analyze the implementation of the class action mechanism in environmental pollution cases based on Decision Number 29/Pdt.G/2023/PN.Skh and to evaluate its effectiveness in providing legal protection and restoring the rights of affected communities. This research employs normative legal research using statute approach, case approach, and conceptual approach. The findings indicate that the class action mechanism in the aforementioned decision fulfilled the requirements of numerosity, commonality, typicality, and adequacy of representation as regulated under Supreme Court Regulation (PERMA) Number 1 of 2002. Procedurally, the class action proved effective in enhancing access to justice, ensuring judicial efficiency, and strengthening the protection of the constitutional right to a good and healthy environment. However, its substantive effectiveness remains dependent on the fulfillment of formal requirements, the quality of evidence presented, and the consistent application of environmental law principles by judges. Therefore, the class action mechanism constitutes an important instrument in environmental law enforcement, yet it requires consistent regulatory support and judicial practice to achieve optimal ecological justice.